2007
DOI: 10.1111/j.1365-3156.2006.01784.x
|View full text |Cite
|
Sign up to set email alerts
|

How much fat is necessary to optimize lumefantrine oral bioavailability?

Abstract: Summarybackground Artemether-lumefantrine (AL) is the only fixed, artemisinin-based combination antimalarial drug which is registered internationally and deployed on a large scale. Absorption of the hydrophobic lipophilic lumefantrine component varies widely between individuals and is greatly increased by fat coadministration; but patients with acute malaria are frequently nauseated and anorexic, making dietary advice difficult to comply with. The aim of this study was to describe the doseresponse relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 12 publications
4
125
0
1
Order By: Relevance
“…24 The difference might be explained by possible variations in food intake, 26 as the levels of lumefantrine blood concentrations may increase 16-fold in patients who took the drug with fatty food compared with without fat. 27,28 Age-based dosage schedules of ALu might also explain the unpredictable blood concentrations of lumefantrine, since the dose per kg may vary widely between patients, as reported for the CQ/SP combination. 29 This underscores the need to monitor the rate of adherence to treatment guidelines by providers as well as treatment schedules among patients in rural areas when implementing ALu treatment on a wide scale in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…24 The difference might be explained by possible variations in food intake, 26 as the levels of lumefantrine blood concentrations may increase 16-fold in patients who took the drug with fatty food compared with without fat. 27,28 Age-based dosage schedules of ALu might also explain the unpredictable blood concentrations of lumefantrine, since the dose per kg may vary widely between patients, as reported for the CQ/SP combination. 29 This underscores the need to monitor the rate of adherence to treatment guidelines by providers as well as treatment schedules among patients in rural areas when implementing ALu treatment on a wide scale in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The full contents of each sachet were mixed with at least 50 ml of cow's milk (equivalent to 2 g of fat), as fat has been reported to increase the bioavailability of PQ tetraphosphate (25,41). The volume of milk used was based on previous experience with its palatability and association with nausea in PNG children as well as on the amount of fat found to maximize the absorption of lumefantrine, another highly lipophilic antimalarial drug, in healthy adults (5).…”
Section: Methodsmentioning
confidence: 99%
“…Chromatographic data (peak area ratio of ART/ARM) were processed using the LAB Solution software package (version 5; Shimadzu, Japan). Responses from analysis of samples containing three different ART concentrations (5,200, and 2,000 g/ liter) and one ARM concentration (1,000 g/liter) spiked into five separate plasma samples were used to determine matrix effects (ion suppression/enhancement), absolute recovery, and process efficiency (32), which were between 90% and 98%, 82% and 93%, and 86% and 91%, respectively. The assay intraday RSDs were 9.3, 7.2, and 3.7% and interday RSDs were 9.5, 7.1, and 6.5% at 5, 200, and 2,000 g/liter, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Oral absorption of this highly lipophilic drug is 16-fold enhanced when taken with a fatty meal. It has been shown that 1.3 g of fat (best taken as milk) is sufficient to improve lumefantrine bioavailability [55]. In contrast to halofantrine 5, lumefantrine 6 is not associated with dangerous cardiac side effect [56].…”
Section: Halofantrinementioning
confidence: 99%